Faktor - Faktor perpustakaan SMK Negeri 1 Singaraja Mengadopsi Aplikasi SLiMS: Automasi Perpustakaan - I Putu Asoka Kamadhuk; Tuty Maryati; Santana Sembiring (Universitas Pendidikan Ganesha, 2026)
Libraries are institutions that provide information services to support educational, research, and recreational needs within society. Along with the development of information technology, libraries need to implement automation systems to improve the effectiveness and efficiency of library services. One of the most widely used library automation systems is Senayan Library Management System (SLiMS). This study aims to identify the factors that encouraged the Library of SMK Negeri 1 Singaraja to adopt SLiMS and to examine the benefits and challenges encountered during its implementation. This research employed a descriptive qualitative method with informants selected through purposive sampling. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of SLiMS was motivated by the completeness of its features and support from the school administration. The use of SLiMS assists librarians in collection management, circulation services, information retrieval, and library report preparation more effectively and efficiently than manual systems. In addition, the Online Public Access Catalog (OPAC) feature has the potential to facilitate users in searching for library collections. However, several challenges were identified, including limited human resources, inadequate facilities and infrastructure, and the ongoing adaptation process to the newly implemented system. Therefore, continuous evaluation and system development are necessary to optimize the utilization of SLiMS in supporting school library services.